Success Analysis of Academic Information System (SIAKAD) Using Delone and Mclean Models (Case Study of STIHPADA Palembang) - Mawarti Mawarti; Iin Seprina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Academic Information System (SIAKADSTIHP) is a legal information system in high schools (ISIKADSTIHP). It is necessary to measure the success of the implementation of Siakad. In this study, researchers analyzed the success of academic information systems using the Delone and McLean models by measuring using 6 variables, namely Information Quality, System Quality, Service Quality, Use, User Satisfaction, and Net Benefit which aims to determine the success factors of academic information systems. The sample in this study amounted to 100 respondents. The data analysis method used is quantitative analysis method using validity test, reliability test, normality test, multicollinearity test, F test and T test. The research data uses an instrument in the form of a questionnaire and is processed using statistical product and service solution (SPSS) software.